P284 Prophylactic medication for the prevention of endoscopic recurrence after ileocolonic resection in Crohn's disease: a prospective study based on clinical risk stratification. (21st January 2022) - Arkenbosch, J H; Beelen, E M J; Dijkstra, G; Romberg-Camps, M; Duijvestein, M; Hoentjen, F; van der Marel, S; Maljaars, P W J; Jansen, S; de Boer, N K; West, R; Horjus, C; et al.
Abstract: Background: In patients with Crohn's disease (CD), postoperative prophylactic medication based on clinical risk stratification is recommended in international guidelines to prevent recurrence after ileocolonic resection (ICR). This study aimed to evaluate the risk of endoscopic recurrence after implementation of a predefined management algorithm after ICR incorporating clinical risk stratification. Methods: In this multicenter, prospective clinical cohort study, CD patients (≥16 years) were included who were scheduled for ICR and gave informed consent. Endoscopy-guided treatment (no prophylactic medication directly after ICR) was recommended in patients at low risk (LR) of postoperative recurrence, and prophylactic medication (immunosuppressant/biological) in high risk (HR). HR was defined as ≥1 risk factor: smoking, penetrating disease, re-resection. Clinical and histologic risk factors for endoscopic recurrence (Rutgeerts' score ≥i2) were assessed using logistic regression models and ROC curves based on predicted probabilities. Results: In total 213 CD patients were included (median age 34.5 years, 65.3% women): 93 (43.7%) at LR and 120 (56.3%) at HR (smoking 45 (21.3%); penetrating disease 51 (23.9%); re-resection 51 (23.9%)). Adherence to the proposed management algorithm was 65%; 76/93 (81.7%) in the LR (no prophylaxis) and 61/120 (50.8%) in the HR population (prophylaxis). Endoscopic recurrence in LR patients was 69% without prophylaxis versus 48% with prophylaxis (p=0.070); in HR 78% without prophylaxis versus 55% with prophylaxis (p=0.019). Clinical risk stratification corresponded with an area under the curve (AUC) of 0.64 (95%CI 0.55–0.73) (Figure 1). Clinical factors combined with histology (active inflammation, granulomas, plexitis in resection margins) increased the AUC to 0.69 (95% CI 0.61–0.88) (Figure 1). Conclusion: This prophylactic medication algorithm in CD patients based on clinical risk stratification after ICR, results in an absolute risk reduction of endoscopic recurrence of 23% in HR versus 21% increase in LR patients in whom medication is omitted. For this latter population, further refinement of risk stratification is required, and may include histologic assessment.